Design and Mechanism Study of 6c, a Novel Artesunate Derivatives, for Anti-Hepatocellular Carcinoma - Xiong SS (Journal of Hepatocellular Carcinoma)
Shang-Shang Xiong Departments of Pharmacology, School of Pharmacy, Qingdao University Medical College, Shandong, People’s Republic of ChinaCorrespondence: Shang-Shang Xiong, Email 17355138325@163.comObjective: Artesunate can inhibit the proliferation of various tumor cells and has practical value in developing anti-tumor drugs. However, its biological activity against hepatocellular carcinoma is weak. The efficacy of its anti-tumor effect needs to be improved.Methods: 11 compounds of three types were designed and synthesized. Their antitumor activity was detected by MTT assay in vitro and subcutaneous xenograft model in vivo. Then, DCFH-DA probe detection and NAC intervention experiments were used to detect ROS levels. The ferroptosis inhibitor (Liproxstatin-1) was used to study the effect of compound 6c in inducing ferroptosis. Western blot was used to observe the expression of apoptosis-related proteins. The ability of 6c to induce apoptosis was detected by Annexin V-FITC/PI double staining and Hoechst 33342 staining experiment. The effect of 6c on cycle arrest was detected by flow cytometry. Molecular simulations of several hybrids with vascular endothelial growth factor receptor 2 (VEGFR-2) and Transferrin receptor protein 1 (TFR1) were performed using MOE molecular docking software.Results: A series of new artemisinin-4-(4-substituted phenoxy) pyridine derivatives were synthesized and their anticancer activities were tested in three lines of hepatocellular carcinoma (HCC) cells. Among the hybrid hits with anticancer activity, a representative 6c compound increased the reactive oxygen species (ROS) level in hepatocellular carcinoma cells and activated mitochondrial apoptosis and ferroptosis, leading to cell cycle arrest at G2/M phase. Molecular docking shows the binding of 6c compound to oncogenic vascular endothelial growth factor receptor 2 (VEGFR-2) and Transferrin receptor protein 1 (TFR1) that are overexpressed in malignant epithelial tumors.Conclusion: Taken together, our identification of the promising compound 6c may hold developmental potential for therapy of hepatocellular carcinoma. Keywords: hepatocellular carcinoma, artesunate, phenoxy-pyridine, hybridization, reactive oxygen species, apoptosis, docking